Menelisik Pelaporan Pajak Online Pada Usaha Mikro Kecil Menengah (UMKM) - Thahir, Fera Firyal; Nasaruddin, Fadliah; Tenriwaru, Tenriwaru (Patria Artha Journal of Accounting dan Financial Reporting, 2020)
The government continues to increase the existing tax potential by carrying out tax modernization in the form of online tax reporting (e-filling). This method is expected to facilitate business tax reporting. However, the reality on the ground shows that some of the small business actors are still unfamiliar with this method because there is still a manual process detected by the tax service provider. The purpose of this study is to determine the dynamics of online tax reporting that is applied to micro, small and medium enterprises (MSMEs) in fulfilling tax obligations as taxpayers. The basis of this research is qualitative with descriptive research type. This research method uses qualitative descriptive and data collection is done by observation, interviews, and documentation. From the results of the research conducted showed that not all taxpayers especially MSMEs use the online tax reporting system, but the online implementation system has been running well and shows consistency that it is mandatory to use a sustainable online system. There have been many taxpayers who feel the benefits of using the online system but there are still some taxpayers who have not felt it, depending on the convenience of each individual. Many taxpayers still lack understanding and feel some obstacles in online reporting. Therefore, in-depth socialization is applied so that the parties served and those served are able to optimize the online system.